Society, utopia and education in Ivan Illich (Psicologia USP, 2006)
In this essay the author emphasizes the connection between the Ivan Illich critic to schooling and his forceful critic to the consumer society and the automation of human life. The arguments of Illich were revised and connected to some philosophical movements and thinkers of the XX century. These ones also are critical with the ways of life produced by a particular version of the Enlightenment.